Maternal mortality of women with opioid-use during pregnancy in England: investigating bias in a cohort of linked mother-baby hospital records - Ruth Blackburn (International Journal of Population Data Science, 2018)
Introduction Opioid-addiction is a major public health threat, with rates of drug misuse related deaths increasing in North America and England. Linkage within and between administrative data datasets is important for capturing determinants and outcomes but this vulnerable population is highly susceptible to linkage error, which can result in inaccurate estimates.